Perlindungan Hukum Bagi Nasabah dalam Perjanjian Kredit Bank terkait Risiko yang Timbul Akibat Pandemi Covid-19 - Budiman, Haris; Akhmaddhian, Suwari; Dialog, Bias Lintang; Anugrah, Dikha; Fernanda, Adam Banyu (Fakultas Hukum, Universitas Boyolali, 2024)
In the era of modern economic life, banking institutions in Indonesia have a very crucial role in the national financial system. Services provided by the bank to the public are money transfer services, collection services, savings and loan services and others. The condition of the banking world in Indonesia has undergone many changes from time to time. This study aims to find out how to regulate legal protection for bank customers and how to form legal protection for customers in credit agreements related to risks arising from the covid-19 pandemic. This study uses a juridical-normative research method. The results of the study show that the regulation of legal protection for customers during the Covid-19 disaster is the Civil Code, Bank Indonesia Regulations, Consumer Protection Laws and Financial Services Authority Regulations. The implementation of legal protection for customers against the COVID-19 pandemic is quite good. This is indicated by the Bank's compliance with all forms of regulations made by regulators including the government. The conclusion from this research is that the policy and implementation of law enforcement in legal protection for customers in a state of the Covid-19 pandemic disaster is carried out quite well by the Bank. The suggestion from the author is that there should be more detailed regulations regarding customers when experiencing a disaster or pandemic and it is hoped that banking institutions carry out the mandate of the Financial Services Authority Regulation.